Assessment of Farmers’ Knowledge towards Sustainable Agricultural Practices (SAP) in Manipur (Indian Journal of Extension Education, 2025)
This study explored disparities in farmers’ knowledge of sustainable agricultural practices between valley and hilly districts of Manipur, conducted across four districts (Senapati, Churachandpur, Imphal East, and Thoubal) from 2021 to 2023. A total of 320 respondents were selected using a multi-stage random sampling method. The study measured knowledge across six areas: agronomic practices, soil and water conservation, nutrient management, pest control, disease control, and waste recycling. Results revealed that valley districts (Imphal East and Thoubal) had significantly higher knowledge (mean index = 45.07) compared to hilly districts (Senapati and Churachandpur) with a mean index of 30.76. Valley districts excelled in practices like crop rotation and water harvesting, while hilly areas showed lower knowledge, particularly in pest management and water conservation. Information sources such as social media played a critical role, especially in hilly districts. The study highlights the need for region-specific interventions and tailored extension services to address knowledge gaps and promote sustainable farming practices.